Examination – the mean of information provision of investigation - Лук’янчиков, Євген Дмитрович; Лук’янчиков, Борис Євгенович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Within the framework of the new Criminal procedure code it is explored the tasks and types of the examination as an investigative action. It is made the comparative analyze of legal regulation of this investigative action in the CPC of Russia, Ukraine and the others countries.